2021
DOI: 10.1002/rcm.9128
|View full text |Cite
|
Sign up to set email alerts
|

INFERYS rescoring: Boosting peptide identifications and scoring confidence of database search results

Abstract: Database search engines for bottom‐up proteomics largely ignore peptide fragment ion intensities during the automated scoring of tandem mass spectra against protein databases. Recent advances in deep learning allow the accurate prediction of peptide fragment ion intensities. Using these predictions to calculate additional intensity‐based scores helps to overcome this drawback.Here, we describe a processing workflow termed INFERYS™ rescoring for the intensity‐based rescoring of Sequest HT search engine results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 30 publications
2
49
0
Order By: Relevance
“…CHIMERYS™ was recently developed by MSAID and makes use of accurate fragment spectrum predictions trained on millions of spectra, which allows to utilize additional spectral properties such as relative signal intensities for drastically improved identification rates and accuracy. 12…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CHIMERYS™ was recently developed by MSAID and makes use of accurate fragment spectrum predictions trained on millions of spectra, which allows to utilize additional spectral properties such as relative signal intensities for drastically improved identification rates and accuracy. 12…”
Section: Introductionmentioning
confidence: 99%
“…CHIMERYS TM was recently developed by MSAID and makes use of accurate fragment spectrum predictions trained on millions of spectra, which allows to utilize additional spectral properties such as relative signal intensities for drastically improved identification rates and accuracy. 12 Implementation of all these innovations allowed us to reach unprecedented sensitivity, proteome coverage and improved throughput, which potentially reduces missing values, and allows novel biological insights. In our analytical platform, we combine recent technological innovations in liquid chromatography, mass spectrometry and data analysis to further improve the depth of analysis as illustrated in Figure 1A.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that the incorporation of expected fragment ion intensities and retention times into database scoring can improve the number and confidence of peptide identifications. ,,, This approach is often referred to as rescoring. Briefly, raw mass spectrometry data is searched initially without filtering for a desired false discovery rate (FDR).…”
Section: Resultsmentioning
confidence: 99%
“…Acquired Orbitrap Exploris 480 .raw DDA files were processed with Proteome Discoverer 2.5 software (Thermo Fisher Scientific) using a two-step Sequest HT search algorithm and INFERYS rescoring node. 19 Further analysis was done using R scripts. 20 The Skyline software package was used to extract and analyze peptide peak areas.…”
Section: Methodsmentioning
confidence: 99%